The Causal Relationship of Problems and Guidelines for Increase Accounting Performance of Blue Flag Store Pracharat - Upping, Phetphrairin; Mettathamrong, Jakret; Chaichana, Charinee; Kesorn, Thanit (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This research aimed 1) to study problems and guidelines for increase accounting performance of Blue Flag Store Pracharat and 2) to study the direct and indirect of the bookkeeping and tax payment effect to problems and guidelines for increase accounting performance of Blue Flag Store Pracharat. This study is a quantitative research and the sample of the research is the entrepreneur of the Blue Flag Store Pracharat in Sakon Nakhon province, amount 681 entrepreneurs. The researcher used a questionnaire as a research instrument to collecting a data and was analyzed by the structural equation model. The result found that the problems and guidelines for increase accounting performance of Blue Flag Store Pracharat consists: a problems of knowledge and understanding of account summary, a problem of lost documents and the important guidelines is the government sector should support the Blue Flag Store Pracharat in various dimension. The result of the study on direct and indirect effect found that the direct effect consists: accounting information, knowledge of taxation and government personnel. The indirect effect consists: accounting documents and methods, staff, accounting tools, tax payment and government personnel.